Controlled synthesis of trimetallic nitrogen-incorporated CoNiFe layered double hydroxide electrocatalysts for boosting the oxygen evolution reaction. Issue 20 (27th April 2022) - Nguyen, Anh Thi Nguyet; Kim, Minji; Shim, Jun Ho
Abstract : A trimetallic nitrogen-incorporated CoNiFe exhibited good catalytic properties toward the oxygen evolution reaction, e.g., high stability and low overpotential (318 mV at 10 mA cm −2 ). Abstract : The development of non-precious trimetallic electrocatalysts exhibiting high activity and stability is a promising strategy for fabricating efficient electrocatalysts for the oxygen evolution reaction (OER). In this study, trimetallic nitrogen-incorporated CoNiFe (N–CoNiFe) was produced to solve the low OER efficiency using a facile co-precipitation method in the presence of ethanolamine (EA) ligands. A series of CoNiFe catalysts at different EA concentrations were also investigated to determine the effects of the ligand in the co-precipitation of a trimetallic system. The introduction of an optimized EA concentration (20 mM) improved the electrocatalytic performance of N–CoNiFe dramatically, with an overpotential of 318 mV at 10 mA cm −2 in 1.0 M KOH and a Tafel slope of 72.2 mV dec −1 . In addition, N–CoNiFe shows high durability in the OER process with little change in the overpotential ( ca. 16.0 mV) at 10 mA cm −2 after 2000 cycles, which was smaller than that for commercial Ir/C (38.0 mV).